Integrated metabonomic–proteomic studies on blood enrichment effects of Angelica sinensis on a blood deficiency mice model - Yongli Hua; Wangling Yao; Peng Ji; Yanming Wei (Pharmaceutical Biology, 2017)
Context: Angelica sinensis (Oliv.) Diels (Umbelliferae) (AS) is a well-known Traditional Chinese Medicine (TCM) that enriches and regulates the blood. Objective: An integrated metabonomic and proteomic method was developed and applied to study the blood enrichment effects and mechanisms of AS on blood deficiency (BD) mouse model. Materials and methods: Forty mice were randomly divided into the control, BD, High-dose of AS (ASH), Middle-dose of AS (ASM), and Low-dose of AS (ASL) groups. BD model mice were established by injecting N-acetylphenylhydrazine (APH) and cyclophosphamide (CTX) (ip). The aqueous extract of AS was administered at three dose of 20, 10, or 5 g/kg b. wt. orally for 7 consecutive days before/after APH and CTX administration. Gas chromatography–mass spectrometry (GC-MS) combined with pattern recognition method and 2D gel electrophoresis (2-DE) proteomics were performed in this study to discover the underlying hematopoietic regulation mechanisms of AS on BD mouse model. Results: Unlike in the control group, the HSP90 and arginase levels increased significantly (p < 0.05) in the BD group, but the levels of carbonic anhydrase, GAPDH, catalase, fibrinogen, GSTP, carboxylesterase and hem binding protein in the BD group decreased significantly (p < 0.05). Unlike the levels in the BD group, the levels of these biomarkers were regulated to a normal state near the control group in the ASM group. Unlike in the control group, l-alanine, arachidonic acid, l-valine, octadecanoic acid, glycine, hexadecanoic acid, l-threonine, butanoic acid, malic acid, l-proline and propanoic acid levels increased significantly (p < 0.05) in the BD group, the levels of d-fructose in the BD group decreased significantly (p < 0.05). The relative concentrations of 12 endogenous metabolites were also significantly affected by the ASL, ASM, and ASH treatments. Notably, most of the altered BD-related metabolites were restored to normal state after ASM administration. Conclusion: AS can promote hematopoietic activities, inhibit production of reactive oxygen species, regulate energy metabolism, increase antiapoptosis, and potentially contribute to the blood enrichment effects of AS against APH- and CTX-induced BD mice.